2004
DOI: 10.1162/15353500200403184
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Respiratory-Gated Micro-CT Imaging in Small-Animal Oncology Models

Abstract: Micro-computed tomography (micro-CT) is becoming an accepted research tool for the noninvasive examination of laboratory animals such as mice and rats, but to date, in vivo scanning has largely been limited to the evaluation of skeletal tissues. We use a commercially available micro-CT device to perform respiratory gated in vivo acquisitions suitable for thoracic imaging. The instrument is described, along with the scan protocol and animal preparation techniques. Preliminary results confirm that lung tumors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Compensation for both cardiac and ventilatory motion is essential for successful pulmonary imaging. Cavanaugh et al have demonstrated ventilatory-gated micro-CT with exposure integration periods of 100 ms. 5 But as is demonstrated in Fig. 5, the cardiac motion can have a substantial impact on the surrounding lung tissue.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compensation for both cardiac and ventilatory motion is essential for successful pulmonary imaging. Cavanaugh et al have demonstrated ventilatory-gated micro-CT with exposure integration periods of 100 ms. 5 But as is demonstrated in Fig. 5, the cardiac motion can have a substantial impact on the surrounding lung tissue.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3] However, cardiopulmonary studies have been limited. 4,5 Since the image noise is proportional to ͑⌬x͒ −2 , where ⌬x is the dimension of the isotropic voxel, the signal-to-noise ratio (SNR) will decrease significantly over that typical in clinical settings if the x-ray exposure to the animal is held constant relative to that in the clinical setting. 1,2,6 At the same time, the physiological motion in the mouse is at least 10ϫ faster than humans.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the non-invasive nature of our technique, imaging the same animal repeatedly over time is easily achieved. Other researchers have used ventilators to force the animals to breathe at a defined rate, 12,13 an invasive approach which requires the animals be intubated by experienced veterinary technicians. The use of an external pressure sensor avoids the need for an invasive measurement of airway pressure, which might alter the normal breathing pattern.…”
Section: A Advantages Of Respiratory-gated Micro-ct Of Freebreathingmentioning
confidence: 99%
“…Cavanaugh et al investigated lung tumors in intubated and respirated rats using an output signal from the respirator to initiate image acquisition just after peak inhalation. 12 Although lung tumors were detected, the respiration-induced motion was not eliminated in this study, as the images were acquired beginning just after peak inhalation and acquiring during exhalation over the full range of motion of the lungs ͑from peak capacity to fully deflated͒. During this portion of the respiratory cycle, the lungs, diaphragm, and ribs undergo sufficient positional changes to cause motion artifacts in the micro-CT image.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-CT may therefore be an important tool for research involving periapical bone lesions in small animals (von Stechow et al 2003). It provides highresolution images (Cavanaugh et al 2004) and permits the assessment of periapical lesions in a multi-planar fashion (von Stechow et al 2003). Micro-CT provides two-(2D) and three-dimensional (3D) images of the sample , and is noninvasive (Balto et al 2000).…”
Section: Introductionmentioning
confidence: 99%